2018
DOI: 10.1186/s13065-018-0395-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular recognition of flunarizine dihydrochloride and β-cyclodextrin inclusion complex by NMR and computational approaches

Abstract: BackgroundFlunarizine dihydrochloride (FLN) is used in the prophylactic treatment of migraine, vertigo, occlusive peripheral vascular disease and epilepsy. Cyclodextrins (CDs) are chiral, truncated cone shaped macrocycles known for their inner hydrophobic and outer hydrophilic site. They form complexes with hydrophobic drug molecules and enhance the solubility and bioavailability of such compounds by enhancing drug permeability through mucosal tissues. NMR spectroscopy and computational docking have been recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The coixol-CDP inclusion compound appeared as irregular long plates ( Figure 4(E) ). Significant morphological differences suggested that the molecules changed lattice arrangement, forming a new phase, indicating the successful synthesis of the CDP and coixol-CDP inclusion compound (Upadhyay and Ali 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…The coixol-CDP inclusion compound appeared as irregular long plates ( Figure 4(E) ). Significant morphological differences suggested that the molecules changed lattice arrangement, forming a new phase, indicating the successful synthesis of the CDP and coixol-CDP inclusion compound (Upadhyay and Ali 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the H-3 are situated near the wider rim while the H-5 are placed near the narrower rim of the cavity (Figure 3). The upfield shift of H-3 and H-5 has been attributed to the magnetic anisotropy effect in the β-CD cavity due to the inclusion of groups rich in π-electrons [27]. The ∆δ of H-3 is significantly lower than that of H-5 , indicating that a total inclusion takes place.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown that symptoms of AHC can be improved with the use of Flunarizine (Cordani et al, 2021 ; Kusunoki et al, 2020 ). Flunarizine is a selective calcium channel entry blocker with calmodulin binding properties and histamine H1 blocking activity (Upadhyay & Ali, 2018 ). While this drug has mostly been used in Italy and Japan, these studies have shown reduction in symptom severity and frequency of hemiplegic attacks (Kusunoki et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%